El acceso a la información sobre organismos modificados genéticamente (OMG). La utilización confinada informada, la liberación voluntaria informada y la comercialización informada de OMG (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2010)
The main focus of this article is a brief description on a specific kind of scientific and research activities with positive involvements in the advance of science itself, which might also cause eventually a negative impact on the environment and on the public health. It refers to the biotechnology activities which involve Genetically Modified Organisms (GMOs). The demand for the accessible public information, the efficiency and transparency of the authorisation procedures for the deliberate release and placing on the market of GMOs, the information content analysis and its effects, are the legal requirements to test. The importance and significance of a democratic and informed society on biotechnological aspects is the key for the citizen participation on their aspects and to keep citizens informed about and involved in environmental matters.